2020
DOI: 10.1515/ijamh-2019-0208
|View full text |Cite
|
Sign up to set email alerts
|

Study of epidemiological determinants of undernutrition among adolescent girls in urban slums of Berhampur, Odisha: a cross-sectional study

Abstract: BackgroundAdolescent girls are vulnerable to many problems, undernutrition being the most common. This results in growth restriction resulting in stunting, wasting, underweight and last but not the least iron-deficiency anaemia. Nutritional needs are high during puberty which later leads to complications during pregnancy and its outcomes.Materials and methodsA field based cross-sectional study was carried out to assess the nutritional status of the girls and to determine the various factors responsible for und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Previous studies have informed that clusters with problems with the nutritional status of children under five are often found in slum areas or flats (Ahsan et al, 2017;De Vita et al, 2019). The relationship of the percentage of the household that occupies livable houses with the prevalence of stunted toddlers applies in general, not only to the nutritional status of toddlers, including adolescents (Mohanty and Panda, 2020). Figure 5 is the scatter plot between the prevalence of stunted toddlers versus the percentage of the population who smoke in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have informed that clusters with problems with the nutritional status of children under five are often found in slum areas or flats (Ahsan et al, 2017;De Vita et al, 2019). The relationship of the percentage of the household that occupies livable houses with the prevalence of stunted toddlers applies in general, not only to the nutritional status of toddlers, including adolescents (Mohanty and Panda, 2020). Figure 5 is the scatter plot between the prevalence of stunted toddlers versus the percentage of the population who smoke in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have informed that clusters with problems with the nutritional status of children under ve are often found in slum areas or ats (Ahsan et al, 2017;De Vita et al, 2019). The relationship of the percentage of the household that occupies livable houses with the prevalence of stunted toddlers applies in general, not only to the nutritional status of toddlers, including adolescents (Mohanty and Panda, 2020). Figure 5 is the scatter plot between the prevalence of stunted toddlers versus the percentage of the population who smoke in Indonesia.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in India and Pakistan have reported significantly higher rates of thinness. Mohanty and Panda (2022) reported that among 160 adolescent girls, the rate of nutritional disorders was 61,3%, of which 90% suffered from anemia. According to the researcher, this was due to the lack of awareness among young women related to limited government programs.…”
Section: Nutritional Statusmentioning
confidence: 99%